Legal and Sustainable Development Impacts of Major Oil Spills - Olawuyi, Damilola S (Consilience, 2013)
Oil spills trigger the application of several interrelated national, regional, and international laws and regulations that provide windows of redress for victims. This paper provides a summary of the legal and sustainable development principles at play where oil spills occur. It provides a simplified synopsis of the relevant principles of international environmental law through which victims of oil spillage can seek compensation. It also highlights the absence of a comprehensive convention on safety standards for oil platforms in international laws applicable to oil spillage.